Spectrum of germline rb1 mutations and clinical manifestations in retinoblastoma patients from thailand - Duangnate Rojanaporn (2019)
© 2018 Molecular Vision. Purpose: Retinoblastoma (RB) is a retinal tumor that most commonly occurs in children. Approximately 40% of RB patients carry germline mutations in the RB1 gene. RB survivors with germline mutations are at increased risk of passing on the disease to future offspring and of secondary cancer in adulthood. This highlights the importance of genetic testing in disease management and counseling. This study aimed to identify germline RB1 mutations and to correlate the mutations with clinical phenotypes of RB patients. Methods: Genomic DNA was extracted from peripheral blood mononuclear cells isolated from 52 RB patients (27 unilaterally and 25 bilaterally affected probands). Mutations in the RB1 gene, including the promoter and exons 1–27 with flanking intronic sequences, were identified by direct sequencing. The samples with negative test results were subjected to multiplex ligation-dependent probe amplification (MLPA) to detect any gross mutations. A correlation of germline RB1 mutations with tumor laterality or age at diagnosis was determined for RB patients. Age at diagnosis was examined in regard to genetic test results and the presence of extraocular tumor extension. Results: Germline RB1 mutations were detected in 60% (31/52) of patients. RB1 mutations were identified in 92% (22/25) of bilateral RB patients, and a high rate of germline RB1 mutations was found in unilateral RB cases (33% or 9/27). Whole gene and exon deletions were reported in five patients. Twenty-three distinct mutations as a result of base substitutions and small deletions were identified in 26 patients; seven mutations were novel. Nonsense and splicing mutations were commonly identified in RB patients. Furthermore, a synonymous mutation was detected in a patient with familial RB; affected mutation carriers in this family exhibited differences in disease severity. The types of germline RB1 mutations were not associated with age at diagnosis or laterality. In addition, patients with positive and negative test results for germline RB1 mutations were similar in age at diagnosis. The incidence of extraocular tumors was high in patients with heritable RB (83% or 5/6), particularly in unilateral cases (33% or 3/9); the mean age at diagnosis of these patients was not different from that of patients with intraocular tumors. Conclusions: This study provides a data set of an RB1 genotypic spectrum of germline mutations and clinical phenotypes and reports the distribution of disease-associated germline mutations in Thai RB patients who attended our center. Our data and the detection methods could assist in identifying a patient with heritable RB, establishing management plans, and informing proper counseling for patients and their families.